Coffee brand equity.: Brand complexity from image and positioning to consumer experience. - Quinde Sari, Freddy Richard; Cahuasquí Cevallos, Edwin Marcelo (SATHIRI, 2022)
The brand value is consolidated as influential, respectable and commercial from the functional and emotional, this research aims to discuss the complexity of the brand from the cognition and conviction of the Imbabura and Carchi coffee consumer. To address the issue of cognition and conviction, a quantitative approach was necessary. The statistical exercise carried out admits the alternative hypothesis: the conviction indices (quality and image) are positively and significantly related to the cognition indices (notoriety and loyalty), managing to explain the reasons why each of the brands studied obtained their position in the brand value ranking (Brand Equity). Thus, the market of Carchi and Imbabura is led by Nescafé, followed by Si Café, Minerva, Juan Valdez and Oro. These 5 companies take advantage of the perceptive scenario that 12 coffee brands leave raised, determining a complex scenario between the perceived image of quality and consumer loyalty. Nescafé has proportional indexes of brand value like Si Café and Minerva, while the brand value achieved by Juan Valdez emphasizes the perception of image and quality. It is concluded that the tastes, needs and preferences of the consumers surveyed show that the behavior of buying coffee after the external influence of the marketing effort has the path of cognition, image to accept conviction. Therefore, the importance of strengthening the cognitive and conviction indices is focused on the construction of a brand value that, in turn, also affects the creation of the value of the product as the key to commercial success in this market.